2023
DOI: 10.1002/ptr.7850
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of proanthocyanidins and anthocyanidins

Abstract: Proanthocyanidins (PA) are polyphenol compounds that are widely distributed in the bark, fruit core, skin, or seeds of various plants. Anthocyanidins are water-soluble natural pigments widely found in plants. They are all flavonoids, a major coloring substance in plants and fruits. In recent years, research into PA and anthocyanins has become increasingly popular because of their excellent anti-oxidation, scavenging of reactive oxygen free radicals and other physical and chemical activities, and their anti-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 152 publications
0
8
0
Order By: Relevance
“…DFR is the key enzyme in anthocyanin biosynthesis, it converts dihydrokaempferol, converts dihydrokaempferol, dihydroquercetin, or dihydromyricetin (DHK, DHQ or DHM, respectively) into leucoanthocyanidins, which are further converted by ANS into other anthocyanidins, modified by glycosylation, acylation, and methylation (Figure 1) [4] and transported by GST and the multidrug and toxic compound extrusion (MATE) transport system into the vacuole [5][6][7]. There are hundreds of unique anthocyanins and many enzymes involved in their modifications; however, these late modification pathways are mostly unknown [8]. The transcriptional regulation of anthocyanin late biosynthesis genes and transporters is mostly conducted by three types of transcription factors (TFs)-myeloblastosis (MYB), basic helix-loop-helix (bHLH), and WD40, which subsequently directly activate/repress other structural genes and downstream TFs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…DFR is the key enzyme in anthocyanin biosynthesis, it converts dihydrokaempferol, converts dihydrokaempferol, dihydroquercetin, or dihydromyricetin (DHK, DHQ or DHM, respectively) into leucoanthocyanidins, which are further converted by ANS into other anthocyanidins, modified by glycosylation, acylation, and methylation (Figure 1) [4] and transported by GST and the multidrug and toxic compound extrusion (MATE) transport system into the vacuole [5][6][7]. There are hundreds of unique anthocyanins and many enzymes involved in their modifications; however, these late modification pathways are mostly unknown [8]. The transcriptional regulation of anthocyanin late biosynthesis genes and transporters is mostly conducted by three types of transcription factors (TFs)-myeloblastosis (MYB), basic helix-loop-helix (bHLH), and WD40, which subsequently directly activate/repress other structural genes and downstream TFs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids can be divided into several groups based on chemical structures. Notably, isoflavonoids, proanthocyanidins, and stilbenes, often overlooked have been proven effective in enhancing human health [ 129 131 ]. In the present study, we identified eleven phenylalanine ammonia-lyases (PALs), four cinnamate 4-hydroxylases (4CHs) and ten 4-coumarate-CoA ligases (4CLs) involving in producing common precursors cinnamoyl CoA and p-coumaroyl CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Proanthocyanidins (PC), also known as condensed tannins, are a group of natural bioflavonoid compounds formed via the condensation of flavan-3-ol structural units [ 1 , 2 , 3 ]. Natural PC is commonly found in a variety of plants, such as grapes, cocoa, apples, blueberries, hawthorn, raspberries, and beans, primarily in their skins, cores, and stalks [ 4 ], with higher concentrations in plant tissues [ 5 ]. Proanthocyanidin molecules contain multiple phenolic hydroxyl structures that can provide hydrogen atoms to neutralize free radicals and competitively bind to them, effectively interrupting free radical chain reactions.…”
Section: Introductionmentioning
confidence: 99%